Uma leitura discursiva sobre os modos de funcionamento do silêncio no livro didático de Língua Portuguesa - Lima, Flágila Marinho da Silva (2015)
This present work aims to reflect about silence in the process of reading proposed by the Schoolbook, it is based on the analysis of activities and modules in a Portuguese Language Schoolbook. It is grounded on the postulates of Pechêux’s Discourse Analysis and aims to discuss how the silence constitutes senses alternating from interdiction and also stimulation to polysemy of discourse in the Schoolbook. Its corpus was constituted of two Portuguese Language Schoolbooks, Elementary II, from the “Coleção Diálogo” of FTD editor. In order to do the analysis, textual interpretation activities were analyzed aiming to verify the silence functioning based on the interdiction of the imaginary reader-subject and the control of the sense. We also analyzed two modules of the school book in order to observe the silencing in them. Our initial hypotheses is that he silence guides the constitution of the senses in these manuals, since it interdicts the access of the subject to different senses, guiding it to the interpretation and reducing it to a mere copy causing the imaginary reader-subject has no opening for interpretation gestures. Thus, these manuals understand sense as something already done and completed and the silence works by signalizer ideological positions of the Schoolbook. The results show that he activities related to reading, in the school books, are on the level of paraphrase without instigating, in the most part of the questions analyzed, a passage towards the polysemy, blocking the student’s perception of plurality of senses which might be linked to the text. On this position, the book is inserted in a discursive formation of unique senses, shaped subjects and, consequently, in an ideology which understands language as transparent. It is also possible notice that the constitutive silence is the source of discursive and ideological affiliations about the black, white and Indian representation since they are inserted in a dominant ideology which understands the indian as “good salvage”, the black people are folkloric are the white one is always related to work.